Taxation and incarceration in Guatemala: Prisons, protection rackets, and citizenship - Fontes, Anthony Wayne (European Review of Latin American and Caribbean Studies, 2023)
This article explores the making of carceral citizenship in Guatemala through an ethnographic analysis of la talacha – informal prison taxation schemes. Taxation is a key technology of citizenship. Tax enforcement mechanisms, the distribution of tax burdens, citizens’ willingness to pay, and their expectations of what they should get in return all make taxation an essential lens through which to understand state formation and citizens’ perceptions of and relations with one another. In Guatemala, where organized crime competes with and subsumes state institutions in ways that profoundly impact everyone, the state is only one of many entities claiming the right to tax, at turns competing and colluding with its underworld. These blurred dynamics are hyper-distilled in the country’s prison system, where state-prisoner networks tax the imprisoned population in the name of collective survival and elite profits. Based on extended ethnographic fieldwork behind bars, I show how la talacha sets the terms of carceral citizenship by organizing prisoner-state co-governance, reifying the prison’s socioeconomic hierarchies, and shaping inmates' relationships with the world beyond the prison. Resumen: Fiscalidad y encarcelaciones en Guatemala: Prisiones, extorsiones y ciudadanía Este artículo explora la construcción de la ciudadanía carcelaria en Guatemala a través de un análisis etnográfico de la talacha: esquema informal de tributación carcelaria. La fiscalidad es una tecnología clave de la ciudadanía. Los mecanismos de aplicación de impuestos, la distribución de las cargas fiscales, la disposición de los ciudadanos a pagar y sus expectativas de lo que deberían obtener a cambio hacen de la fiscalidad una lente esencial a través de la cual entender la formación del Estado y las percepciones de los ciudadanos y las relaciones entre ellos. En Guatemala, donde el crimen organizado compite con las instituciones estatales y las subsume en formas que afectan profundamente a todos, el Estado es sólo una de las muchas entidades que reclaman el derecho a tributar, compitiendo y confabulando a su vez con el hampa. Estas dinámicas difusas se hiperdestilan en el sistema penitenciario del país, donde las redes entre el Estado y los presos gravan a la población reclusa en nombre de la supervivencia colectiva y los beneficios de las élites. Basándome en un extenso trabajo de campo etnográfico entre rejas, muestro cómo la talacha establece los términos de la ciudadanía carcelaria organizando el cogobierno entre presos y Estado, reificando las jerarquías socioeconómicas de la prisión y configurando las relaciones de los reclusos con el mundo más allá de la cárcel.